Localization in bundles of uniform spaces (1990)
In sheaf theory we have at our disposal the so called "germination process" by means of which a sheaf can be obtained, in a natural manner, from data provided by a presheaf. Essentially, "germination" is a stalk producing mechanism that requires direct systems, whose colimits are the desired stalks of the sheaf.